Development of AR-Based Interactive Reading Media to Support SDG 4 and Improve Student Learning Independence at SDN Lemahireng - Shinta Anugrah Ikhtiarini; Bagas Kurnianto Kurnianto (Jurnal Penelitian Pendidikan IPA, 2026)
This study aimed to develop and examine the feasibility and effectiveness of an Augmented Reality (AR)-Based Reading Book learning media on science learning outcomes related to the human digestive system for fifth-grade students at SDN Lemahireng. The study employed a Research and Development (R&D) method using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 30 fifth-grade students selected from one class during the product trial. Data were collected through pretest and posttest, observations, interviews, questionnaires, and documentation. Data analysis included normality, homogeneity, N-Gain, and paired sample t-test. The validation results showed that the media was highly feasible, with scores of 90% from material experts and 96% from media experts. The average student score increased from 62.63 in the pretest to 82.00 in the posttest, with an N-Gain score of 0.52 in the moderate category. The paired sample t-test indicated a significant improvement in learning outcomes (t = 10.87, Sig. < 0.05). In addition, students gave positive responses toward the media, reaching 89.69%. In conclusion, the AR-Based Reading Book learning media is feasible and effective in improving students’ science learning outcomes.